2022
DOI: 10.1007/s10639-022-11050-3
|View full text |Cite
|
Sign up to set email alerts
|

The webcam and student engagement in synchronous online learning: visually or verbally?

Abstract: Given that video conferencing serves as a crucial means for remote teaching, the current study investigated higher education students’ (non)use of webcams and engagement in synchronous online courses. Three phases were studied: (1) A state of engagement; (2) antecedents that influence it; and (3) consequences of engagement. The cross-sectional online survey encompassed 3,610 students. Results indicated that visual and verbal engagement were only slightly related to each other. Structural equation modelling rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 98 publications
1
6
0
5
Order By: Relevance
“…Session sizes were also relatively small due to limited participant availability. Students in synchronous online classes frequently report class size as a determining factor for when they turn their webcams on (Bedenlier et al, 2021; Händel et al, 2022), and class size is relevant to establishing both social presence and accountability. As such, class size will be important to investigate further.…”
Section: Discussionmentioning
confidence: 99%
“…Session sizes were also relatively small due to limited participant availability. Students in synchronous online classes frequently report class size as a determining factor for when they turn their webcams on (Bedenlier et al, 2021; Händel et al, 2022), and class size is relevant to establishing both social presence and accountability. As such, class size will be important to investigate further.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, research has shown that integrating collaborative activities, group discussions, and peer interaction in the classroom enhances students' engagement with the material presented by teachers [47,48]. Moreover, requiring students to use webcams is important for maintaining their attention to the course content and allowing teachers to observe and assess their understanding and progress through visual cues such as facial expressions, hand raises, eyebrow raises, and head poses [49][50][51]. Similarly, there is evidence that demonstrates that feedback from teachers is critical in terms of making the feedback regular and providing it through video instead of text so that the teaching and social presence of the teacher can facilitate learners' engagement [52,53].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Engagement is the ability to spend attentional resources on task-related stimuli and ignore external interference [1]. As a fundamental aspect of cognition, engagement ability plays a crucially important role in the operational environment [2].…”
Section: Introductionmentioning
confidence: 99%